REDUCING DEFECTIVE OF ROLL M-70 PRODUCT ON CASTING PROCESS - -, Sukirman; Primandhika, Enden; B, ,Huda Muhamad; M, Deros B (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
Statistical process control (SPC) is a method of monitoring the production process with the goal of maintaining product quality during the production process. Thus, once the problems (variables)have resulted, the repair process can be immediately identified and carried out.However, in some cases, the application of SPC is not maximized. This was caused by the lack of a systematic procedure that was usedto guide the operator in applying statistical process control. Therefore, this study offers a systematic procedure to guide the operator in applying SPC. Systematic procedure is performed with the literature study and direct observation in manufacturing companies. In order to apply statistical process control, several statistical tools are accommodated according to their needs and objectives. Thus,it results systematic application of SPC procedure which consists of 15 steps and is divided into two concepts.Indicator is applied to determine the systematic procedure to qualify whether the test is applicable and can improve the ability of the process. Definition of applicable is able to guide the operator in applying SPC and stabilize the process. Systematic procedure have undergone testing at the casting factory. Systematic procedures otherwise applicable and may improve the ability of the improved process.